The Multiplicity Of Syntactic Aspects Between The Indications Of Meaning And The Requirements Of The Workmanship (Journal of the College of Basic Education, 2024)
The research sheds light on the approach of some Arabic grammarians who adopted the grammatical rule, that grammatical rule that adopted incomplete induction as a method that led the Arabic grammar to enter the industry, so grammar became a complex process for the learner who wanted Arabic in order to access knowledge of the glorious Qur’an. At a time when the artisans used to color the Arabic text, but rather went to me the Qur’anic texts to achieve those rules in support of the school to which this or that grammar belongs, and this interpreter belongs to this or that theological doctrine.